Clinical occurrence and radiographic diagnosis of distal limb lameness in equine - HIMANI, HIMANI; KUMAR, ASHWANI; ANAND, ARUN; SINGH, NAVDEEP; UPPAL, VARINDER; MOHINDROO, JITENDER (The Indian Journal of Animal Sciences, 2019)
The objectives of this study was to evaluate the hospital occurrence of various radiographic lesions of the distal limb (bones and joints) lameness in equine and to evaluate the role of nerve and joint blocks for the localization of lameness in equine. All the equine lameness cases (117), presented during the one year study period that were subjected to radiographic evaluation, were investigated. Out of these, 20 equine lameness cases were subjected to systematic evaluation including nerve / joint blocks to confirm, whether the clinically or radiographically detected lesion was the primary cause for the lameness or not. Out of 117, 78 equine (66.67%), were diagnosed with 124 radiographic lesions involving 101 limbs. The majority (62.8%) of the equines had single radiographic lesion, whereas the remaining animals were detected with multiple lesions involving one (15.4%) or more limbs (21.8%). Majority cases of equine lameness were recorded in winter season. Highest per cent lesions were recorded in hoof region (25.81%) with more common involvement of fore feet (68.75%) and in mares (54.54%). Hock and fetlock regions were second (22.6%) and third (21.8%) most common regions for occurrence of equine lameness. Fetlock joint of hindlimb (63%) was more commonly affected than that of the forelimb. In this study, 16 nerve / joint blocks were applied in 15 horses and these were found helpful in confirming the lameness lesions in 66.7% cases. In conclusion, high prevalence of multiple lesions involving one or more limb poses great diagnostic challenge. Forelimb hoof and the hock were most frequently involved in distal limb lameness in equine. Periostitis and arthritis were most prevalent lameness causing lesions in equine. Physical examinations, nerve/ joint bocks and radiography complement each other in confirming the site of lesion causing lameness.